2017
DOI: 10.1186/s12906-016-1529-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antimalarial activity of crude extracts and solvent fractions of leaves of Strychnos mitis in Plasmodium berghei infected mice

Abstract: BackgroundMalaria is a major public health problem in the world which is responsible for death of millions particularly in sub-Saharan Africa. Today, the control of malaria has become gradually more complex due to the spread of drug-resistant parasites. Medicinal plants are the unquestionable source of effective antimalarials. The present study aimed to evaluate antiplasmodial activity and acute toxicity of the plant Strychnos mitis in Plasmodium berghei infected mice.MethodsStandard procedures were employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 31 publications
(45 reference statements)
9
68
0
Order By: Relevance
“…The dose-dependent reduction in parasitemia levels produced by the methanol aerial extract of Alysicarpus glumaceus (average parasitemia 20.46 ± 1.31, 15.48 ± 1.37 and 12.26 ± 0.79 at 250, 500, and 1,000 mg/kg, respectively), is an indication of the extracts ability to inhibit the proliferation of Plasmodiumparasite in mice (Figure 3). The current finding agreed with other reports on medicinal plants used for malaria, such as Indigofera spicata, 8 Strycnos mitis 21 and Trema orientalis. 23 The oral median lethal dose was estimated to be greater than 5,000 mg/kg as there was no mortality recorded after the first and second phases of the acute toxicity study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The dose-dependent reduction in parasitemia levels produced by the methanol aerial extract of Alysicarpus glumaceus (average parasitemia 20.46 ± 1.31, 15.48 ± 1.37 and 12.26 ± 0.79 at 250, 500, and 1,000 mg/kg, respectively), is an indication of the extracts ability to inhibit the proliferation of Plasmodiumparasite in mice (Figure 3). The current finding agreed with other reports on medicinal plants used for malaria, such as Indigofera spicata, 8 Strycnos mitis 21 and Trema orientalis. 23 The oral median lethal dose was estimated to be greater than 5,000 mg/kg as there was no mortality recorded after the first and second phases of the acute toxicity study.…”
Section: Resultssupporting
confidence: 93%
“…This could be due to recrudescence Key: + = present, -= absent of P. berghei parasites after apparent cure. 21 According to Mbah et al, 22 the curative property of potential antimalarial agents of plantbased origin should be detectable during screening for antimalarial activity. Thus, the ability of the extract to decrease parasitemia levels and prolong survival time suggests that it has antimalarial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Plant extracts are considered active when reduction or percentage suppression in parasitemia is ≥ 30% or signi cant prolonging the survival time of treated mice compared to the vehicle control (38)(39)(40). Thus, the leaf latex of A. weloensis was found to be active against P. berghei infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemistry: Phytochemical screening of hydromethanolic leaves of S. mitis showed the presence of different secondary metabolites like alkaloids, tannins saponins, flavonoids Terpenoids, Steroid, phenols and glycosides which is comparable with other species of the plant. 55,56 Safety and toxicity: Selamawit et al, 55 investigated the acute toxicity study of S. mitis indicated that both hydromethanolic and aqueous extract of S. mitis leaves caused no mortality up to 2000mg/kg oral doses within the first 24 hours as well as for the following 14 days and the experimental mice who ingested the crude aqueous, chloroform and methanol leaf extracts of S. mitis also did not show any indication of gross physical or behavioral changes.…”
Section: Parts Used Leafmentioning
confidence: 99%
“…The N-hexane fraction and the higher two doses (200mg/kg and 400mg/kg) of chloroform and aqueous fraction of S. mitis leaves protected the mice from body weight loss as compared to negative control after four day suppressive test, this investigation is comparable with antiplasmodial activity of other species of Strychnos, S. usambarensis, S. icaja, S. variabilis, S.angolensis and S. memecyloides. 55,57…”
Section: Parts Used Leafmentioning
confidence: 99%